2022
DOI: 10.5194/acp-2022-137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Updated trends of the stratospheric ozone vertical distribution in the 60° S–60° N latitude range based on the LOTUS regression model

Abstract: Abstract. This study presents an updated evaluation of stratospheric ozone profile trends in the 60° S–60° N latitude range over the 2000–2020 period, using an updated version of the Long-term Ozone Trends and Uncertainties in the Stratosphere (LOTUS) regression model that was used to evaluate such trends up to 2016 for the last WMO Ozone Assessment (2018). In addition to the derivation of detailed trends as a function of latitude and vertical coordinates, the regressions are performed with the data sets avera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, adding three more years between the original version of LOTUS and the update still did not produce statistically significant trends in LSO for the recovery phase. Possibly, the ozone recovery period is not yet long enough to detect statistically significant LSO trends in the LOTUS regression analysis (Godin-Beekmann et al, 2022). The attribution of all necessary regressors is also important to increase the robustness of the trend.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…However, adding three more years between the original version of LOTUS and the update still did not produce statistically significant trends in LSO for the recovery phase. Possibly, the ozone recovery period is not yet long enough to detect statistically significant LSO trends in the LOTUS regression analysis (Godin-Beekmann et al, 2022). The attribution of all necessary regressors is also important to increase the robustness of the trend.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In the upper stratosphere (above 10 hPa), the ozone abundance declined by about 4-8% between 1980 to the late 1990s due to a continuous increase in stratospheric chlorine loading (e.g., Steinbrecht et al, 2017;WMO, 2018), but since the late 1990s it has been steadily recovering (Ball et al, 2018;WMO, 2018). This recovery is statistically robust according to various analyses of satellite observations and model simulations (Harris et al, 2015;Steinbrecht et al, 2017;Ball et al, 2018;Godin-Beekmann et al, 2022). The main driver of the upper stratospheric ozone recovery is the reduction of halogen loading.…”
mentioning
confidence: 85%
“…According to Ball et al [42], the influence of a consequent increase in tropospheric ozone in the tropics may hide an ever-existing decrease in the lower stratosphere. Indeed, a significant decrease in ozone in the tropics (20 ° S -20 ° N) around 35 hPa has been observed by Godin-Beekmann et al [43] and an increase in tropospheric ozone over the tropics was found by the work of Thompson et al [44] and Leventidou et al [45]. Furthermore, the positive value observed for this trend could be related to the cooling of the upper stratosphere resulting from the increase in greenhouse gas (GHG) emissions, which slows the gas phase ozone loss mechanisms in that region (Chapter 5 of the WMO report, 2018) [40].…”
Section: Trendsmentioning
confidence: 78%
“…However, additional predictors may be required when using the regression for local stations, as suggested by Van Malderen et al (2021) and SPARC/IO3C/GAW (2019). A few recent studies used the LOTUS regression to derive local trend profiles at specific stations (Godin-Beekmann et al, 2022;Bernet et al, 2021;Van Malderen et al, 2021), but they did not investigate the use of additional local predictors. Furthermore, all studies using the LOTUS regression concentrate on latitudes between 60 • S and 60 • N and on stratospheric ozone profiles.…”
Section: Regression Predictorsmentioning
confidence: 99%